2013
DOI: 10.1016/j.regpep.2013.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Arginine vasopressin, via activation of post-junctional V1 receptors, induces contractile effects in mouse distal colon

Abstract: The aim of this study was to analyze whether arginine vasopressin (AVP) may be considered a modulator of intestinal motility. In this view, we evaluated, in vitro, the effects induced by exogenous administration of AVP on the contractility of mouse distal colon, the subtype(s) of receptor(s) activated and the action mechanism. Isometric recordings were performed on longitudinal and circular muscle strips of mouse distal colon. AVP (0.001 nM-100 nM) caused concentration-dependent contractile effects only on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 42 publications
2
11
0
Order By: Relevance
“…In control animals, the contractile effect of Ang II was dependent on AT 1 receptor activation, as pretreatment with Losartan, AT 1 receptor antagonist, significantly antagonized Ang II effect, and PD123319, AT 2 receptor antagonist was ineffective. This is line with previous studies addressing AT 1 receptors as the major effectors of Ang II‐related effects and AT 2 receptors, even if expressed, seems uncoupled to the contractile mechanisms in physiological conditions . In DNBS‐treated animals, the contractile effect of Ang II was still antagonized by the AT 1 receptor antagonist, indicating that Ang II‐induced contractile effect is once more mediated by AT 1 receptors.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In control animals, the contractile effect of Ang II was dependent on AT 1 receptor activation, as pretreatment with Losartan, AT 1 receptor antagonist, significantly antagonized Ang II effect, and PD123319, AT 2 receptor antagonist was ineffective. This is line with previous studies addressing AT 1 receptors as the major effectors of Ang II‐related effects and AT 2 receptors, even if expressed, seems uncoupled to the contractile mechanisms in physiological conditions . In DNBS‐treated animals, the contractile effect of Ang II was still antagonized by the AT 1 receptor antagonist, indicating that Ang II‐induced contractile effect is once more mediated by AT 1 receptors.…”
Section: Discussionsupporting
confidence: 92%
“…Each preparation was tested with a single antagonist, unless otherwise stated. Concentrations of the drugs used were determined from previous experiments and from literature.…”
Section: Methodsmentioning
confidence: 99%
“…V 1a and V 1b receptors couple to Gq whereas V 2 receptors couple to the Gs pathway (Koshimizu et al, 2012). The V 1a receptor is expressed by smooth muscle cells where its activation causes vasoconstriction, increased intestinal motility and bladder contraction (Holmquist et al, 1991;Mastropaolo et al, 2013;Thibonnier et al, 1999;Uvelius et al, 1990). The V 2 receptor, on the other hand, is responsible for the antidiuretic action of AVP via effects on the collecting ducts of the kidneys (Thibonnier et al, 1999;Treschan and Peters, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…; Mastropaolo et al . ). Preliminary studies showed that the effects of AVP were concentration dependent and that the responses were maximal using 10 n m AVP.…”
Section: Methodsmentioning
confidence: 97%